The Antioxidant Characteristics of The Liquid Smoke of Cocoa Shell ( Theobroma cacao, l ) In Different Water Content Variations - I Ketut Budaraga; Eva Susanti; Asnurita Asnurita; Elliza Nurdin; Ramaiyulis Ramaiyulis (Jurnal Ilmu dan Teknologi Terapan Pertanian, 2019)
Agricultural and plantation wastes, especially cocoa plants, have not been widely used, although in some conditions they have potential as animal feed ingredients and raw materials for composting. So needs a program potential utilization of waste produced by the plant cocoa is cocoa shell waste such as being liquid smoke. Liquid smoke is a natural food preservative. One of the advantages of liquid smoke is antioxidant compounds. This study aims to know the antioxidant activity of cocoa shell liquid smoke on a variety of different water content. This research is an experimental quantitative descriptive method so that an analysis of the antioxidant activity of liquid smoke from cocoa peel is obtained. The results showed that the liquid smoke of cocoa peels at a moisture content of 25%, 20%, 15%, and 10% had strong antioxidant activity because the IC 50 values obtained were below 50 ppm.